Habits and self-assessed quality of life, negative intrusive thoughts and depressed mood in patients with prostate cancer: a longitudinal study. (3rd September 2017) - Bock, David; Angenete, Eva; Bjartell, Anders; Carlsson, Stefan; Steineck, Gunnar; Stranne, Johan; Thorsteinsdottir, Thordis; Wiklund, Peter; Haglind, Eva
Abstract: Objective: The aim of this study was to evaluate the association of self-assessed preoperative physical activity, alcohol consumption and smoking with self-assessed quality of life, negative intrusive thoughts and depressed mood after radical prostatectomy. Materials and methods: The Laparoscopic Prostatectomy Robot Open (LAPPRO) trial was a prospective, controlled, non-randomized longitudinal trial of patients ( n  = 4003) undergoing radical prostatectomy at 14 centers in Sweden. Validated patient questionnaires were collected at baseline, and 3, 12 and 24 months after surgery. Results: Preoperative medium or high physical activity or low alcohol consumption or non-smoking was associated with a lower risk of depressed mood. High alcohol consumption was associated with increased risk of negative intrusive thoughts. Postoperatively, quality of life and negative intrusive thoughts improved gradually in all groups. Depressed mood appeared to be relatively unaffected. Conclusions: Evaluation of preoperative physical activity, tobacco and alcohol consumption habits can be used to identify patients with a depressed mood in need of psychological support before and immediately after surgery. Quality of life and intrusive thoughts improved postoperatively.